ANALYSIS OF THE SITUATION IN THE ORGANIC PRODUCTION SEGMENT IN BOSNIA AND HERZEGOVINA AND THE REGION - Zijada Rahimić; Emina Resić (Zbornik Radova Ekonomskog Fakulteta u Istočnom Sarajevu, 2023)
The aim of this paper is to identify the basic characteristics of organic production in the agricultural sector of Bosnia and Herzegovina in terms of determining the scope, trends and flows in the selected time period. In terms of competitiveness, special emphasis is placed on the position of Bosnia and Herzegovina in the region. That is, a comparative review with the countries of the region according to the available indicators of organic production within the data of the Research Institute for Organic Production (FiBL). The analysis is focused on the changes of relevant indicators for Bosnia and Herzegovina and the countries of the region in the period from 2010 to 2020. The analysis was made using methods of dynamic analysis (index numbers, average annual rate of change, trend) and comparison methods. The results of the research can be a starting point for policy makers in support of the development of the agricultural sector.